PENGARUH PROMOSI FLASH SALE, DAYA TARIK IKLAN DAN MOTIVASI BELANJA HEDONIS TERHADAP PERILAKU PEMBELIAN IMPULSIF (Studi Pada Pengguna Shopee di Jakarta Timur) - Jimmy Ferdian Kurnia (2022)
This type of research conducted by researchers is quantitative research that aims to find out the influence of flash sale promotion, advertising appeal, and hedonic shopping motivation on impulsive buyings. This study used a sample of 100 respondents from the population in East Jakarta who used Shopee e-commerce in making online purchases. The sampling method uses non probability sampling using the purposive sampling method. The data collection conducted in this study used online questionnaires using Google Form which was then shared through the Line, WhatsApp, Twitter, Instagram, and Telegram. This research uses PLS analysis techniques (Partial Least Square) with SmartPLS 3.0 application. The results obtained from this research are: (1) Flash sale promotion variables have a positive and significant effect on impulsive buying with the value of the path coefficient 0.256. (2) Variable ad attractiveness positively and significantly affects impulsive buying with path coefficient value 0.385. (3) Hedonic shopping motivation variables have a positive and significant effect on impulsive buying with path coefficient value 0.309.